Elastic and Inelastic Scanning Tunneling Spectroscopy on Iron-Based Superconductors - Jandke, Jasmin Maria (Experimental Condensed Matter Physics / Karlsruher Institut für Technologie, Physikalisches Institut, 2019)
Within this work, the pairing mechanism of conventional (Pb) and unconventional superconductors (SrFe2(As1-xPx )2 , FeSe, FeSe/STO) was investigated experimentally by means of elastic and inelastic tunneling spectroscopy at temperatures down to 30 mK. The distinction between elastic and inelastic contributions to tunneling data was elaborated. The results help to identify conventional (phonon-mediated) and unconventional (e.g. spin-?uctuation mediated) superconductivity.